Toll‐like receptor 3 is an endogenous sensor of cell death and a potential target for induction of long‐term cardiac transplant survival. Issue 10 (22nd April 2021) - Zhao, Jiangqi; Huang, Xuyan; Mcleod, Patrick; Jiang, Jifu; Liu, Winnie; Haig, Aaron; Jevnikar, Anthony M.; Jiang, Zhenyu; Zhang, Zhu‐Xu
Abstract : Inflammation posttransplant is directly linked to cell death programs including apoptosis and necrosis. Cell death leads to the release of cellular contents which can promote inflammation. Targeting of these pathways should be an effective strategy to prevent transplant rejection. Toll‐like receptor 3 (TLR3) is emerging as a major endogenous sensor of inflammation. In this study, we assessed the role of TLR3 on cell death and transplant rejection. We showed that TLR3 is highly expressed on mouse microvascular endothelial cell (ECs) and the endothelium of cardiac grafts. We demonstrated that TLR3 interacting with dsRNA or self‐RNA triggered apoptosis and necroptosis in ECs. Interestingly, TLR3‐induced necroptosis led mitochondrial damage. Inhibition of the mitochondrial membrane permeability molecule Cyclophilin D prevented necroptosis in ECs. In vivo, endothelium damage and activities of caspase‐3 and mixed lineage kinase domain‐like protein were inhibited in TLR3 −/− cardiac grafts compared with C57BL/6 grafts posttransplant ( n  = 5, p  < .001). Importantly, TLR3 −/− cardiac grafts had prolonged survival in allogeneic BALB/c mice (mean survival = 121 ± 67 vs. 31 ± 6 days of C57BL/6 grafts, n  = 7, p  = .002). In summary, our study suggests that TLR3 is an important cell death inducer in ECs and cardiac grafts and thus a potential therapeutic target in preventing cardiac transplant rejection. Abstract : This study demonstrates that toll‐like receptor 3 is an important mechanistic mediator of necroptosis and apoptosis in endothelial cells and an effective target for prevention of cardiac transplant rejection.